2009
DOI: 10.1007/s00436-009-1574-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimosquito activity of aqueous kernel extract of soapnut Sapindus emarginatus: impact on various developmental stages of three vector mosquito species and nontarget aquatic insects

Abstract: Aqueous (physiological saline) extracts of seed kernel from seven indigenous plants were initially screened for their antimosquito activity against eggs, larvae of all instars, and pupae of Aedes aegypti. Among various seed kernels tested, the soapnut Sapindus emarginatus (Sapindaceae) extract was found to exhibit, for the first time, a strong antimosquito activity as evident from its ability to inflict 100% mortality of all the developmental stages of A. aegypti. Furthermore, the kernel extract of S. emargina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Especially the first and second instar of this species were more susceptible and bring 100 % mortality to the extract at the 6 to 8 mg/ml, when compared to other larval developmental stages. In a similar study [39] were reported likewise that, the soapnut S. emarginatus has inflicted potent antimosquito activity against all the developmental stages of A. aegypti than other mosquito strains of C quinquefasciatus especially fourth stage larvae and pupae was has less susceptible of soap nut extract. By contrast the Ramanibai et al [40] were reported the strongest Ovicidal, larvicidal and pupicidal activity of A. squamosa aqueous soluble extract against all the developmental stages of A. aegypti, particularly all the larval instar.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Especially the first and second instar of this species were more susceptible and bring 100 % mortality to the extract at the 6 to 8 mg/ml, when compared to other larval developmental stages. In a similar study [39] were reported likewise that, the soapnut S. emarginatus has inflicted potent antimosquito activity against all the developmental stages of A. aegypti than other mosquito strains of C quinquefasciatus especially fourth stage larvae and pupae was has less susceptible of soap nut extract. By contrast the Ramanibai et al [40] were reported the strongest Ovicidal, larvicidal and pupicidal activity of A. squamosa aqueous soluble extract against all the developmental stages of A. aegypti, particularly all the larval instar.…”
Section: Discussionsupporting
confidence: 52%
“…The similar studies Ramanibai et al [40] were also reported that the A. squamosa seed extract also not affected tested aquatic insect C. costatus at their tested concetration. In addition Koodalingam et al [39] were also reported same studies with some disadvantage antimosquito activity of S. emarginatus has produced mortality against two non target aquatic organisms tested, Chironomus costatus (fourth instar larvae) at LC 50 5.71 and LC 50 4.78 and for Diplonychus rusticus (first instar nymphs) at LC 50 9.29 LC 50 8.26 for 24 and 48 h exposed for 24 and 48 h exposed. But in our studies the M. zapota seed has not produced any mortality at tested concentration.…”
Section: Discussionmentioning
confidence: 78%
“…Bansal et al (2009) reported that the 24 h LC 50 values as observed for aqueous extracts for green unripe and yellow ripe fruits were 112.7, 498.2, and 846.3 mg/L and 104.7, 267.7, and 832.2 mg/L for A. stephensi, A. aegypti, and C. quinquefasciatus, respectively. Aqueous (physiological saline) extracts of seed kernel from soapnut Sapindus emarginatus (Sapindaceae) was found to exhibit, a strong antimosquito activity as evident from its ability to inflict 100% mortality of all the developmental stages of A. aegypti (Koodalingam et al 2009). …”
Section: Resultsmentioning
confidence: 98%
“…The crude hexane extract obtained from the leaf of Leucas aspera was tested for the larvicidal activity against Culex quinquefasciatus and Aedes aegypti (Maheswaran et al 2008); the acetone, chloroform, ethyl acetate, hexane, and methanol leaf extracts of Ocimum canum, Ocimum sanctum, and Rhinacanthus nasutus were studied for antifeedant and larvicidal activity against the fourth instar larvae of Spodoptera litura, Aedes aegypti, and Culex quinquefasciatus (Kamaraj et al 2008a). The aqueous extracts of seed kernels of Pongamia glabra, Adenanthera pavonina, and Sapindus emarginatus were found to exhibit effective ovicidal, larvicidal, and pupicidal activity on Aedes aegypti (Koodalingam et al 2009). The crude methanol, dichloromethane, and hexane extracts of Cestrum nocturnum caused mortality on the second, third, and fourth instar larvae of Aedes aegypti (Chandrashekhar et al 2011); the hexane extracts of Aegle marmelos and Andrographis paniculata revealed potential repellent, ovicidal, and oviposition activity against Culex tritaeniorhynchus ; the crude leaf acetone, chloroform, hot water, methanol, petroleum ether, and water extracts of Calotropis procera R.…”
Section: Introductionmentioning
confidence: 99%